The house of the seven gables - Hawthorne, Nathaniel 1804-1864 (New York : A Macfadden-Bartell Book, 1968)
This edition is for readers for whom English is a second language. It can be anyone whos has learned 1,000 words of english.
Glossary.
Keywords: Novelas; Estados Unidos De America; Literatura Norteamericana